The BIM Implementation for Preparing Mutual Check-0 (MC-0) Documents in the Building Development Project of Edusmart Soerojo Hospital Magelang - A’la, Rafi Nurul (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
The development of Building Information Modeling (BIM) technology in the construction sector has been a solution to the problem of preparing planning documents that often occur. It can lower the discrepancy between the value of the planning contract and the value of the building construction implementation contract. The BIM system defines the physical characteristics of a design model into information that can be implemented at several stages of construction work, one of which is Mutual Check 0 (MC-0). Preparing documents (MC-0) on construction projects aims to adjust planning documents in the form of analysis of work items, working drawings, and calculation of the volume of work that affects the contract value. In a short time, the parties involved in construction work, such as contractor service providers and supervisory consultants, need to check the planning volume to match the actual volume of work in the field. In the Edusmart Soerojo Hospital Magelang Building construction project, Building Information Modeling (BIM) is used to check the volume of work. This checking process is assisted by using the Autodesk Revit 2021 software. This study reviews the effectiveness of BIM in preparing documents (MC-0) using a comparative descriptive method, comparing the volume of work in contract documents with the actual volume in the field. This study’s results show a difference between adding and reducing volume in the field. The addition occurred in earthworks and excavation, foundation structure, 1st-floor structure, 2nd-floor structure, roof floor structure, and Ground Water Tank (GWT) work. In contrast, the decrease occurred in the sloof understructure and roof work. The total volume obtained indicates a difference in the contract value of the structural work, which has increased by 9.47%. The initial planning contract value was IDR 5,569,152,785.40, an increase of IDR 527,623,004.49 to IDR 6,096,775,789.89.